Tensile strength and dynamic mechanical analysis of new IPNs based on epoxy resin-polysulphide elastomer - Hanoosh, Widad Salih; Saleh, Hind Mahde (European Journal of Chemistry, 2016)
The toughness of diglycidyl ether of bisphenol, an epoxy resin with polysulphide was investigated. Several interpenetrating polymer networks based on epoxy resin and different weight percentage of polysulphide were prepared and characterized by dynamic mechanical analysis technique. From the result, the glass transition temperature of these systems was lower than glass transition temperature of epoxy alone and also the impact strength was increase with increasing percentage of polysulphide.